2017
DOI: 10.1109/tec.2016.2614526
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Coupling Analysis in a Multichip Paralleled IGBT Module for a DFIG Wind Turbine Power Converter

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available.Copies of full items can be used for personal research or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…13, it can also be understood that even at high airflow rates, faraway chips continue to create a significant cross-heating effect. This is in contrast to the findings in [38] where the authors demonstrated that the chips with a distance of more than 10 mm are no longer thermally coupled with any cooling system. As further research, Fig.…”
Section: ) Electro-thermal Operating Conditionscontrasting
confidence: 85%
“…13, it can also be understood that even at high airflow rates, faraway chips continue to create a significant cross-heating effect. This is in contrast to the findings in [38] where the authors demonstrated that the chips with a distance of more than 10 mm are no longer thermally coupled with any cooling system. As further research, Fig.…”
Section: ) Electro-thermal Operating Conditionscontrasting
confidence: 85%
“…Parallel-connected power modules can start missions with almost the same thermal and electrical parameters at the beginning [19][20][21], but may vary over the entire operational life due to uneven degradation rates of aging. Differences in electrical and thermal parameters of individual devices can cause other failure mechanisms [22,23]. Therefore, if parallel-connected power devices are affected by different load currents, they will undergo different thermal cycles.…”
Section: Aging Mechanism Of the Power Devicementioning
confidence: 99%
“…However, the major drawback of these models is they did not solve thermal coupling problem, which will cause a significant problem in an intelligent power module (IPM). The 3D thermal network is also the proposed to consider both self‐heating and cross‐heating in the device, as detailed in [22–27]. In those network models, thermal behaviour is described using a Foster network, in which the R and C parameters are calculated through curve fitting of data got from FEM.…”
Section: Introductionmentioning
confidence: 99%